Volume kinetics of crystalloid and colloid solutions administered to healthy anesthetized cats - Chien-Hsien Kitty Yang; Xiu Ting Yiew; Robert G. Hahn; William Muir; Carolyn Kerr; Shane Bateman (PLoS ONE, 2025)
This prospective experimental study evaluated the disposition of a crystalloid and a colloid solution in 10 healthy cats under general anesthesia. Each cat was randomly assigned to receive either 20 mL/kg of a balanced isotonic crystalloid solution (PLA) or 5 mL/kg of 6% tetrastarch 130/0.4 solution (T-HES), administered over 15 minutes, in a 2-period, 2-treatment crossover design. Blood samples were collected, and urine output was measured during a 3-hour experimental period. Plasma dilution was calculated using serial hemoglobin concentrations and red blood cell count. Volume kinetics (distribution and elimination) of each fluid were determined using non-linear mixed effects pharmacokinetic modeling software. Data from a previous study with a similar methodology in healthy conscious cats were included in the population kinetic analysis, revealing anesthesia as a significant covariate for k21 (peripheral-to-central intercompartmental rate constant) for PLA and k10 (dilution-dependent first-order elimination rate constant) for T-HES. Cumulative urine output under general anesthesia was approximately 3.5 times lower for PLA and 2.5 times lower for T-HES compared to conscious cats. Overall, our data suggest that the elimination of PLA and T-HES is markedly reduced, and a bolus of PLA produces a short period of plasma expansion with the potential to cause significant peripheral fluid accumulation in cats during general anesthesia.